Brain Structure, Connectivity, and Cognitive Changes Following Revascularization Surgery in Adult Moyamoya Disease. Issue 5 (3rd June 2019) - Kazumata, Ken; Tha, Khin Khin; Tokairin, Kikutaro; Ito, Masaki; Uchino, Haruto; Kawabori, Masahito; Sugiyama, Taku
Abstract: BACKGROUND: The effect of the combined direct/indirect revascularization surgery in Moyamoya disease has not been evaluated sufficiently with regard to cognitive function, brain microstructure, and connectivity. OBJECTIVE: To investigate structural and functional changes following revascularization surgery in patients with moyamoya disease (MMD) through a combined analysis of brain morphology, microstructure, connectivity, and neurobehavioral data. METHODS: Neurobehavioral and neuroimaging examinations were performed in 25 adults with MMD prior to and >12 mo after revascularization surgery. Cognitive function was investigated using the Wechsler Adult Intelligence Scale-III, Trail-Making Test, Wisconsin Card Sorting Test, Continuous Performance Test, Stroop test, and Wechsler Memory Scale. We assessed white matter integrity using diffusion tensor imaging, brain morphometry using magnetization-prepared rapid gradient-echo sequences, and brain connectivity using resting-state functional magnetic resonance imaging (MRI). RESULTS: Cognitive examinations revealed significant changes in the full-scale intelligence quotient (IQ), performance IQ (PIQ), perceptual organization (PO), processing speed, and Stroop test scores after surgery ( P < .05). Enlargement of the lateral ventricle, volume reductions in the corpus callosum and subcortical nuclei, and cortical thinning in the prefrontal cortex were also observed ( P < .05). Fractional anisotropy in the white matter tracts, including the superior longitudinal fasciculus, increased 2 to 4 yr after surgery, relative to that observed in the presurgical state ( P < .05). Resting-state brain connectivity was increased predominantly in the fronto-cerebellar circuit and was positively correlated with improvements in PIQ and PO ( P < .05). CONCLUSION: Revascularization surgery may improve processing speed and attention in adult patients with MMD. Further, multimodal MRI may be useful for detecting subtle postsurgical brain structural changes, reorganization of white matter tracts, and brain connectivity alterations.